GM2 gangliosidoses - Mahuran, Don (Henry Stewart Talks, 2007)
GM2 gangliosidosis: the disease and the associated system of beta-hexosaminidase isozymes, Structure-function relationships, What have naturally occurring mutations told us?, Why is dimerization necessary for activity if both subunits have active sites?, What is the basis for the substrate-specificity differences between the active sites of the two subunits?, Why can only heterodimeric hexosaminidase A hydrolyze GM2 ganglioside?
Reviewed at 2016/01/09, Archived at 2022/03/28